2017
DOI: 10.1101/183376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomes of major renal collecting-duct cell types in mouse identified by single-cell RNA-Seq

Abstract: Prior RNA sequencing (RNA-Seq) studies have identified complete transcriptomes for most renal epithelial cell types. The exceptions are the cell types that make up the renal collecting duct, namely intercalated cells (ICs) and principal cells (PCs), which account for only a small fraction of the kidney mass, but play critical physiological roles in the regulation of blood pressure, extracellular fluid volume and extracellular fluid composition. To enrich these cell types, we used fluorescence-activated cell so… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Coupled with our expression studies (Results) we would like to propose that Slc4a8 is not expressed in the CCD, including the B-intercalated cells. Further support for the absence of Slc4a8 in the cortical collecting duct was reported in a recent study, which indicated that in single cell isolation of CCD cells (A-IC, B-IC and principal cells) Slc4a8 was not detected [31]. Given the complete absence of Slc4a8 mRNA in the CCD [31], it is highly likely that the signal detected in western blots using .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Coupled with our expression studies (Results) we would like to propose that Slc4a8 is not expressed in the CCD, including the B-intercalated cells. Further support for the absence of Slc4a8 in the cortical collecting duct was reported in a recent study, which indicated that in single cell isolation of CCD cells (A-IC, B-IC and principal cells) Slc4a8 was not detected [31]. Given the complete absence of Slc4a8 mRNA in the CCD [31], it is highly likely that the signal detected in western blots using .…”
Section: Discussionmentioning
confidence: 88%
“…Further support for the absence of Slc4a8 in the cortical collecting duct was reported in a recent study, which indicated that in single cell isolation of CCD cells (A-IC, B-IC and principal cells) Slc4a8 was not detected [31]. Given the complete absence of Slc4a8 mRNA in the CCD [31], it is highly likely that the signal detected in western blots using . From a thermodynamic point of view, the parallel activation of pendrin and NHE-2 is equivalent to the coupling of an NBC-like pathway with pendrin, in that both pathways lead to enhanced entry of sodium and chloride in an electroneutral manner.…”
Section: Discussionmentioning
confidence: 88%
“…To overcome these potential problems, it is feasible to dissect only a specific portion of kidney tissues (e.g., proximal tubules or glomeruli) and to dissociate cells with an improved method for increased cell viability, such that the complexity of cell types will be reduced and cell viability will be increased, allowing the rare cell types to be picked up and analyzed. Indeed, Chen et al [76] focused on only collecting duct for scRNA-seq and resolved the A-type intercalated cells, the B-type intercalated cells, principal cells, and hybrid cells that are between A-and B-type intercalated cells in gene expression. This approach gave rise to more precise dissection of cell types or subtypes compared with scRNA-seq of whole kidney, as described in the work by Park et al [79].…”
Section: Perspectivesmentioning
confidence: 99%
“…Chen et al [76] performed scRNA-seq on mouse renal collecting duct cells and created the database from which genes selectively expressed in each cell type of collecting duct can be found. Furthermore, they showed that a small fraction of hybrid cells expressed aquaporin-2 and anion exchanger 1 or pendrin transcripts.…”
Section: Current Studies In the Field Of Kidney Research That Used Scmentioning
confidence: 99%
“…ICs were isolated by fluorescence activated cell sorting from previously characterized transgenic mice that express enhanced green fluorescent protein (EGFP) specifically in these cells (B1-EGFP mice) [35]; no expression was detected in all other renal cell types [1]. In addition, RNA sequencing of isolated EGFP ICs identified P2Y 14 as one of the most expressed genes in these cells, while single cell RNA sequencing showed specific expression of P2Y 14 in type A ICs [36]. Subsequent examination showed that P2Y 14 is located on the apical surface of ICs in contact with the tubular fluid (pre-urine; Fig.…”
Section: Identification Of the P2y 14 Receptor In Collecting Duct Icsmentioning
confidence: 99%